A new Late Jurassic halecomorph fish from the marine Vaca muerta formation, Argentina, southwestern Gondwana - Gouiric Cavalli, Soledad (2016)
The knowledge of Mesozoic fish faunas of the Southern Hemisphere is still inadequate; the diversity and evolution of the Late Jurassic marine ichthyofaunas of Argentina remain unclear. One fish recovered from the Tithonian levels of the Los Catutos Member of the Vaca Muerta Formation, southwestern Argentina was considered a “caturid-like” halecomorph for almost 30 years. Recently, it was proposed that it could belong to the Pachycormiformes. A thorough comparative anatomical study of the material is conducted to test whether it could be included in †Caturidae or †Pachycormidae. The specimen is assigned to †Caturidae as a new genus and species: †Catutoichthys olsacheri (http://zoobank.org/urn:lsid:zoobank.org:act: 6884876C-075C-433B-90B7-74187FC04C26, registered on 1 June 2016). The new taxon is based on a unique character combination, three of which are exclusive to †Catutoichthys olsacheri among caturids–diplospondylous vertebral column with triangular basidorsals and welldeveloped and fan-shaped basiventrals; neural and haemal spines strongly inclined to the body axis at an angle of 14°; a large number of infrahaemals; rounded amioid-type scales with an unornamented free field. The new taxon provides anatomical information useful for further understanding the anatomy and evolution of caturid fishes.